A scoping review of the reasons for and approaches to non-uptake of pertussis and influenza vaccinations in pregnant women in the United Kingdom and Ireland - Stephanie Ann McCarron; Declan Terence Bradley; Nigel David Hart (BMC, 2023)
Abstract Background Pertussis and influenza cause significant morbidity and mortality in pregnancy and the neonatal period. Maternal vaccination in pregnancy would reduce harm, but low vaccine uptake is a concern. This scoping review aimed to understand the reasons for, and approaches, to non-uptake of pertussis and influenza vaccinations in pregnant women in the UK and Ireland. Methods The inclusion criteria of this scoping review consist of pregnant women who avail of pertussis and influenza vaccines in the UK and Ireland. MEDLINE, EMBASE, Web of Science and CINAHL databases were searched in June 2021 and updated in October 2022. Searches were limited to English language reports published after 2011. We followed the Joanna Briggs Institute guidance on scoping reviews. Data were extracted and charted. Results Five themes emerged from the literature. Acceptability, as well as organisational and awareness issues, were overarching themes regarding reasons for and approaches to non-uptake of the vaccines respectively. Other themes included healthcare professional factors, information interpretation and pregnancy-related factors. Conclusions Women need clear, comprehensible information, ideally provided by their healthcare professionals, in a way that is meaningful and addresses their circumstances and risk perceptions. This research will serve as a base for future work that aims behaviour science interventions at the wider pregnant population as well as the target groups that have been identified in this review.